1967
DOI: 10.1002/cber.19671000314
|View full text |Cite
|
Sign up to set email alerts
|

Monosaccharide mit stickstoffhaltigem Ring, XIII. Synthese und Reaktionen von Keto‐piperidinosen

Abstract: 6-Amino-2.3-0-isopropyliden-6-desoxy-~-~-sorbof~anose (ll), fur die zwei Synthesewege aufgefunden wurden, liefert bei saurer Hydrolyse in der Kalte kristallisiertes 6-Amino-6desoxy-L-sorbofuranose-hydrochlorid (17), das nur in stark saurer Losung stabil ist. In alkalischer Losung erfolgt Ringerweiterung zur L-Sorbo-piperidinose 18, die mit dem Piperidein 19 im Gleichgewicht steht. In neutraler Losung bei Raumtemperatur geht das Hydrochlorid 17 uber 18 unter dreifacher Wasserabspaltung quantitativ in 3-Hydroxy-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
1

Year Published

1981
1981
2007
2007

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(45 citation statements)
references
References 18 publications
0
44
0
1
Order By: Relevance
“…General Procedure 2: β-Galactosidase-catalysed glycosylation with 2-acetamido-2-deoxy--glucopyranose (14) as acceptor: Glycosyl donor (150 µmol) and 2-acetamido-2-deoxy--glucopyranose (14) (300 mg, 1.36 mmol, 9 equiv.) were dissolved in 50 m sodium acetate buffer (4 mL) pH 5.0 at 55°C.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…General Procedure 2: β-Galactosidase-catalysed glycosylation with 2-acetamido-2-deoxy--glucopyranose (14) as acceptor: Glycosyl donor (150 µmol) and 2-acetamido-2-deoxy--glucopyranose (14) (300 mg, 1.36 mmol, 9 equiv.) were dissolved in 50 m sodium acetate buffer (4 mL) pH 5.0 at 55°C.…”
Section: Resultsmentioning
confidence: 99%
“…As uniform acceptor substrates 2-acetamido-2-deoxy--glucopyranose (14) as well as allyl 2-acetamido-2-deoxy-α--glucopyranoside (15) were used in the enzymatic glycosylation. Reactions with compound 15 were performed at room temperature for 3 days, while reactions with GlcNAc (14) required 3 h at 55°C.…”
Section: β-Galactosidase Catalysed Glycosylationmentioning
confidence: 99%
See 1 more Smart Citation
“…The key intermediate of this approach is the imine 75, which is easily prepared in eight steps from l-sorbose (an inexpensive sugar) in 64 % overall yield (Scheme 6). 2,3;4,6-Di-O-isopropylidene-α-lsorbofuranose (71) was obtained in one step from l-sorbose in 80 % yield as reported earlier by Paulsen et al [44] A judicious four-step protection-deprotection procedure gave the fully protected furanose 73 (91 % yield from 71), which was subsequently subjected to cleavage of the trityl group upon treatment with HBr in glacial AcOH. The resulting hydroxymethyl group was then oxidized by treatment with DM periodinane in DCM to afford the aldehyde 74 on a large scale (approx.…”
Section: Chiral-pool Starting Materials: Carbohydratesmentioning
confidence: 99%
“…My co-worker, I. Sangster, converted the Reichstein intermediate of vitamin C synthesis, 2,3-0-isopropylidine-a-L-sorbofuranose, into a 6-amino-6-deoxy-Lsorbose [27]. He found that in concentrated hydrochloric acid solution this aminosugar formed an ammonium salt in which the sorbose is in the furanose form with oxygen in the ring.…”
mentioning
confidence: 99%